PROFICIENCY LEVEL AND LANGUAGE LEARNING STRATEGY CHOICE OF ISLAMIC UNIVERSITY LEARNERS IN INDONESIA - Alfian, Alfian (TEFLIN Journal, 2018)
This study explores the relation between language proficiency level and language learning strategy choice of EFL learners at an Islamic university in Indonesia. Two hundred and eighty four participants classified based on their proficiency levels (high, medium, and low) as determined by their achievement results completed the Strategy Inventory for Language Learning (SILL) version 7.0 questionnaires. The findings indicated that there was a linear relationship between proficiency level and strategy use; the higher the proficiency level, the higher the number of strategies employed. Furthermore, it was also found that higher proficiency level learners tended to choose meta-cognitive strategies; they usually managed learning by conscientious planning, monitoring, and evaluating their own learning. The findings also demonstrated that low proficiency level learners were inclined to choose affective strategies, meaning that they were concerned with the emotional requirements such as confidence. The findings of this study provide contribution to further development of existing global theories about language learner strategies, and are beneficial for classroom practice in the Indonesian context, especially in raising EFL teachers' awareness about ways in improving student learning.